Hubungan Pengetahuan Nilai Guna Rekam Medis dengan Perilaku Pengisian Rekam Medis oleh Perawat RSU. Mitra Medika Tanjung Mulia - Dilla Fitria; Sri Agustina Meliala; Aida Sulisna; Alfred Nehe (Lembaga Pengembangan Kinerja Dosen, 2024)
There are eight different uses for medical records: administrative, legal, financial, research, educational, documentation, public health, planning, and marketing. This study aimed to determine the relationship between knowledge about medical records use value and the behavior of filling out medical record documents by nurses in inpatient room at Mitra Medika Hospital Tanjung Mulia Medan in 2023. This is quantitative research with analytic survey design and used cross sectional approach. The statistical test used spearman rank test. The population in this study were all nurses who worked in Inpatient Room of the Hospital with 89 people and all were sampled. The results of Spearman rank test with a confidence level of 95% or alpha (a) = 0.05 obtained a p value = 0.002, it can be concluded that there was a significant relationship (meaningful) between knowledge of the use value of medical records and the behavior of filling out medical record documents. The correlation coefficient obtained through the Spearman rank statistical test or r value was = 0.319. According to cross tabulation, the results of data analysis (statistical test) are p value (significant value) = 0.002 a = 0.05, indicating that there is a meaningful relationship (significant relationship) between knowledge of the value of using medical records and the practice of filling out medical record paperwork. It is suggested that in order to improve the accuracy of filling up medical record documents, respondents broaden their understanding of the importance of medical records and their use by reading books, articles, and other reading materials.